APLIKASI TEST MINAT DAN BAKAT PENERIMAAN SISWA BARU PADA SMK TI GARUDA NUSANTARA CIMAHI MENGGUNAKAN VISUAL BASIC.NET - Nanan Rohman; Yuda Mulya Darmawan (STMIK Mardira Indonesia, Bandung, 2015)
Tests interest made by the school talent for the new students before choosing majors. This test is done to allow participants to determine their potential. Specifically at the level of vocational schools (SMK), held majors or program selection expertise. The test is a tool to obtain data on the behavior of individuals. Interests are activities or tasks that arouse curiosity, attention, and give pleasure or enjoyment. Interests can be an indicator of the strength of a person in a particular area so that he will be motivated to learn and demonstrate high performance. Talent is an innate ability that is a potential that still need to be developed or trained to achieve a skill, knowledge and special skills. In this application there is a menu that is used for administration of the administrator. Administrator is a user who has full access rights to process data that relates to the student and with regard to the test. Against to the system administrator responsible for software applications in order to operate properly. Interest and aptitude test application is built using Microsoft Visual Basic.net as coding editor, Microsoft Access 2007 as database processing software. This software application implemented in IT vocational school Garuda Nusantara Cimahi. Keywords: application; test; interests and talent